Clinical patterns, management and outcomes of shock in children: a five-year review from a tertiary hospital in South-South Nigeria - Areprekumor, Tare-ebi; Onyeka, Chiemere Adaeze; Aladei, Tariere; Obuge, Uselemi D. (International Journal of Contemporary Pediatrics, 2026)
Background: Shock is a life-threatening paediatric emergency marked by inadequate tissue perfusion and rapid progression to organ failure if untreated. Mortality remains high in low- and middle-income countries, where delayed recognition and limited resources hinder optimal care. Septic and hypovolaemic shock predominate in sub-Saharan Africa, often driven by infectious diseases and malnutrition. Understanding local patterns is essential for improving early detection and treatment. Therefore, the study aimed to describe the clinical features, management practices and factors associated with mortality among children admitted with shock to the Children’s Emergency Ward of Federal Medical Centre, Yenagoa. Methods: A retrospective review of children admitted with shock between January 2018 and December 2022 was conducted. Case notes were examined for demographic data, presenting features, laboratory findings, type of shock, interventions and outcomes. Data were analysed using SPSS version 26. Associations were assessed using Chi-square or Fisher’s exact test. Results: Fifty-four cases were identified among 4,453 admissions. Septic shock was the most common type. Severe malnutrition, hypoglycaemia, anaemia, electrolyte derangements, leukocytosis and low oxygen saturation were significantly associated with mortality. Use of intraosseous access and inotropes was linked with poor outcomes, while fluid-only resuscitation had the best survival. All deaths occurred within 48 hours. Conclusions: Septic shock remains the dominant and most fatal form of paediatric shock in this setting. Early recognition, prompt resuscitation and strengthened emergency care systems are critical to improving outcomes.